A preliminary study on the use of alternative chemicals for treatment of wastewater in coal fired power generation / Gunasegran A/L Ramasamy - Ramasamy, Gunasegran (2012)
Hydrated lime is used for pH adjustment as part of the treatment process at the main wastewater treatment plant in Sultan Azlan Shah Power Station, Manjung. Many problems are encountered in usage of hydrated lime mainly in terms of handling. Manual labour is used to load hydrated lime into bag unloader and it is a messy job because some of the chemical spills and gets air borne. This is also a safety concern. The hydrated lime also frequently chokes the outlet of storage silo and is another manual job to clear the blockage. This study is important because replacement of hydrated lime with a suitable alternative chemical can be advantageous for smooth operation of the wastewater treatment plant. In this preliminary study the use of alternative chemicals for pH adjustment was studied using jar tests. The alternative chemicals tested are soda ash, sodium hydroxide and potassium hydroxide. The main criteria in judging the performance of the alternative chemicals are floc size and settling time between pH 9.0 to 9.5. All three chemicals performed well at pH 9.0. Settling time for soda ash increased to 12 minutes at pH 9.5 and was judged to be not suitable. Sodium hydroxide and potassium hydroxide were found to perform well at pH 9.5 with a settling time of four minutes. Amount of sludge generated was compared and found to be slightly higher for sodium hydroxide as compared with hydrated lime. Cost for using potassium hydroxide was calculated to be lowest but it incurs manual labour for charging up. Sodium hydroxide has the second lowest cost and existing pumps can be utilized to prepare the charges. Sodium hydroxide is already available in the wastewater treatment plant for pH adjustment for post neutralization purpose. It is concluded that the alternative chemical of choice suitable for use in the wastewater treatment plant is sodium hydroxide.